Effect of elevated temperature on the bond behavior between near Surface Mounted-Carbon Fiber Reinforced Polymers strips and Recycled Aggregate concrete. (10th August 2020) - Obaidat, Yasmeen Taleb; Barham, Wasim S.; Abdelrahman, Bahaa N.
Highlights: The bond behavior between RA concrete exposed to high temperatures and NSM-CFRP was investigated. RA replacement percentage affect the performance of the bond between concrete and NSM-CFRP. High RA replacement percentage decreases the bonding load and slippage. Abstract: This study investigates the bond behavior between Recycled Aggregate (RA) concrete specimens exposed to high temperatures and Near Surface Mounted-Carbon Fiber Reinforced Polymers (NSM-CFRP) strips. A total of 54 concrete specimens with dimensions of (150 × 150 × 200 mm) were cast using three different concrete mixes (i.e. three diverse concrete strength of 20, 30 and 40 MPa). Two RA replacement ratios were used, 30% and 60%. Specimens with 20 and 40 MPa concrete mixes contain 60% of (RA) were exposed to 23 °C and 600 °C elevated temperatures. Whereas, specimens with 30 MPa concrete mix contain 30% and 60% RA replacement ratio were exposed to 23 °C, 400 °C and 600 °C elevated temperatures. The heat damaged specimens were repaired using double (NSM-CFRP) strips technique and tested under the pullout test in order to study the mechanical behavior of the bond between RA concrete and NSM-CFRP strip. Three different (NSM-CFRP) strips bonded lengths of (100, 150 and 200 mm) were used and three various spacing between the (NSM-CFRP) strips of (0, 50 and 70 mm) were studied. According to the experimental results, RA replacement percentage, elevated temperature value, concrete strength, length of strip as well as the spacing between NSM-CFRP strips significantly affect the performance of the bond between concrete and NSM-CFRP strip. High RA replacement percentage decreases the bonding load and slippage and therefore the bond length needed increases. The use of RA with high strength concrete showed lower reduction in the bonding load compared to the RA concrete specimens with low concrete strength. Using double strips of NSM-CFRP with large spacing enhances the mechanical behavior of the bond between RA concrete and NSM-CFRP strips. The exposure to high temperature decreases the bond load and increases slippage. The failure mode in all specimens was concrete separation.